Switching to fixed-dose bictegravir, emtricitabine, and tenofovir alafenamide from dolutegravir plus abacavir and lamivudine in virologically suppressed adults with HIV-1: 48 week results of a randomised, double-blind, multicentre, active-controlled, phase 3, non-inferiority trial. Issue 7 (July 2018) - Molina, Jean-Michel; Ward, Douglas; Brar, Indira; Mills, Anthony; Stellbrink, Hans-Jürgen; López-Cortés, Luis; Ruane, Peter; Podzamczer, Daniel; Brinson, Cynthia; Custodio, Joseph; Liu, Hui; Andreatta, Kristen; et al.
Summary: Background: Bictegravir, co-formulated with emtricitabine and tenofovir alafenamide, has shown good efficacy and tolerability, and similar bone, renal, and lipid profiles to dolutegravir, abacavir, and lamivudine, in treatment-naive adults with HIV-1 infection, without development of treatment-emergent resistance. Here, we report 48-week results of a phase 3 study investigating switching to bictegravir, emtricitabine, and tenofovir alafenamide from dolutegravir, abacavir, and lamivudine in virologically suppressed adults with HIV-1 infection. Methods: In this multicentre, randomised, double-blind, active-controlled, non-inferiority, phase 3 trial, HIV-1-infected adults were enrolled at 96 outpatient centres in nine countries. Eligible participants were aged 18 years or older and on a regimen of 50 mg dolutegravir, 600 mg abacavir, and 300 mg lamivudine (fixed-dose combination or multi-tablet regimen); had an estimated glomerular filtration rate of 50 mL/min or higher; and had been virologically suppressed (plasma HIV-1 RNA <50 copies per mL) for 3 months or more before screening. We randomly assigned participants (1:1), using a computer-generated randomisation sequence, to switch to co-formulated bictegravir (50 mg), emtricitabine (200 mg), and tenofovir alafenamide (25 mg; herein known as the bictegravir group), or to remain on dolutegravir, abacavir, and lamivudine (herein known as the dolutegravir group), once daily for 48 weeks. The investigators, participants, study staff, and individuals assessing outcomes were masked to treatment assignment. The primary endpoint was the proportion of participants with plasma HIV-1 RNA of 50 copies per mL or higher at week 48 (according to the US Food and Drug Administration snapshot algorithm); the prespecified non-inferiority margin was 4%. The primary efficacy and safety analyses included all participants who received at least one dose of study drug. This study is ongoing but not actively recruiting participants and is in the open-label extension phase, wherein participants are given the option to receive bictegravir, emtricitabine, and tenofovir alafenamide for an additional 96 weeks. This trial is registered with ClinicalTrials.gov, number NCT02603120 . Findings: Between Nov 11, 2015, and July 6, 2016, 567 participants were randomly assigned and 563 were treated (282 received bictegravir, emtricitabine, and tenofovir alafenamide, and 281 received dolutegravir, abacavir, and lamivudine). Switching to the bictegravir regimen was non-inferior to remaining on dolutegravir, abacavir, and lamivudine for the primary outcome: three (1%) of 282 in the bictegravir group had HIV-1 RNA of 50 copies per mL or higher at week 48 versus one (<1%) of 281 participants in the dolutegravir group (difference 0·7%, 95·002% CI −1·0 to 2·8; p=0·62). Treatment-related adverse events were recorded in 23 (8%) participants in the bictegravir group and 44 (16%) in the dolutegravir group. Treatment was discontinued because of adverse events in six (2%) participants in the bictegravir group and in two (1%) participants in the dolutegravir group. Interpretation: The fixed-dose combination of bictegravir, emtricitabine, and tenofovir alafenamide might provide a safe and efficacious option for ongoing treatment of HIV-1 infection. Funding: Gilead Sciences.